Promoting University-Industry Collaboration in Sri Lanka : Status, Case Studies, and Policy Options - Larsen, Kurt (Washington, DC: World Bank, 2016)
Strong science, technology, and innovation links between universities and industry are of critical importance to Sri Lanka as it strives to become an upper-middle-income country.